Primary extraskeletal osteosarcoma of the post-hepatic caudal vena cava in a dog—Case report - Tremolada, Giovanni; Griffin, Lynn; Manchester, Alison C.; Aboellail, Tawfik; Lapsley, Janis M.; Selmic, Laura E. (Frontiers in Veterinary Science, 2023)
Extraskeletal osteosarcoma (EOSA) in dogs is a rare malignant mesenchymal tumor of somatic soft tissues or more commonly visceral organs with a poor prognosis. In dogs, EOSAs have been described arising from multiple locations, but differently from humans, never from a main vessel. In this report, we describe the first case of an EOSA arising from the post hepatic caudal vena cava in a 7 year-old male neutered mix breed dog. This report focuses on the description of the diagnostic challenges to obtain a preoperative diagnosis, highlights the importance of histopathology for a correct diagnosis and introduces a new differential diagnosis for an animal presenting with a suspected thrombus of the vena cava.